Distributed energy resources integration in AC Grids: A family of passivity-based controllers (2019)
This paper presents the design and application of passivity-based control theory for distributed energy resources (DERs) integration through voltage source converters (VSC) in ac single-phase grids. The Hamiltonian representation of these grids facilitates the development of passive controllers that guarantee stability in the sense of Lyapunov for their closed-loop operation. The non- autonomous dynamic modeling of these systems is transformed into an incremental model, which allows solving the tracking as a regulation problem. The main contribution of this paper is in the ability to control the active and reactive power transference between DERs and the ac single-phase grid depending on the availability of the primary energy resource and the capacity of the converters. Simulations results show that all proposed controllers attain the control objective, reaching the same dynamic performance as classical proportional-integral controllers and guaranteeing asymptotic stability. All simulations are developed under the MATLAB/Simulink environment through the SimPowerSystems tool. © 2019 Universitat Politecnica de Valencia. All Rights Reserved.